Diversity of Ancient Woody Species in Urban Forests - Fornal-Pieniak Beata (Folia Forestalia Polonica: Series A - Forestry, 2014)
Mostly parks and forest are the most important ‘green islands’ in urban ecological network. Urban forests are belong to green areas and collected many plant species. The main aim of the article was characteristic of ancient plant species in urban forests in Tarnów. The field studies were carried out in years 2011-2012. It covered 80 phytosociological records on the area 500 m2 in herb layer of urban forests and in forest nature on oak-hornbeam. The results showed that many ancient plant species were growing in urban forest but less than in nature reserves